The Problem of Overcrowding and Its Legal Implications for the Fulfillment of Prisoners' Rights in Correctional Institutions - Emirza Nur Wicaksono (Veteran Law Review, 2026)
This study aims to analyze the problem of overcrowding in correctional institutions and its legal implications for the fulfillment of prisoners' rights in Indonesia. Overcrowding is a serious problem in the correctional system that has the potential to hinder the implementation of correctional guidance and the fulfillment of prisoners' basic rights. This study uses a normative legal research method with a legislative and conceptual approach. Legal materials were obtained through a literature review covering relevant laws and regulations, legal doctrine, and scientific journal articles. The results indicate that correctional institution overcrowding is caused by various legal and non-legal factors, including the dominance of imprisonment in the penal system, the high use of detention in the criminal justice process, and limited correctional facilities and infrastructure. These conditions hamper the fulfillment of prisoners' rights, particularly the rights to humane treatment, health services, correctional guidance, and security. The state has a legal responsibility to guarantee the protection of prisoners' rights, thus necessitating reform of penal policy through the implementation of alternative sentencing and non-prison policies to reduce prison overcrowding. This research provides theoretical contributions to the development of correctional law studies and provides policy recommendations to strengthen a more humane penal system oriented toward human rights protection